Intake of a Ketone Ester Drink during Recovery from Exercise Promotes mTORC1 Signaling but Not Glycogen Resynthesis in Human Muscle - Vandoorne, Tijs; De Smet, Stefan; Ramaekers, Monique; Van Thienen, Ruud; De Bock, Katrien; Clarke, Kieran; Hespel, Peter (Frontiers in Physiology, 2017)
Purpose: Ketone bodies are energy substrates produced by the liver during prolonged fasting or low-carbohydrate diet. The ingestion of a ketone ester (KE) rapidly increases blood ketone levels independent of nutritional status. KE has recently been shown to improve exercise performance, but whether it can also promote post-exercise muscle protein or glycogen synthesis is unknown. Methods: Eight healthy trained males participated in a randomized double-blind placebo-controlled crossover study. In each session, subjects undertook a bout of intense one-leg glycogen-depleting exercise followed by a 5-hour recovery period during which they ingested a protein/carbohydrate mixture. Additionally, subjects ingested a ketone ester (KE) or an isocaloric placebo (PL). Results: KE intake did not affect muscle glycogen resynthesis, but more rapidly lowered post-exercise AMPK phosphorylation and resulted in higher mTORC1 activation, as evidenced by the higher phosphorylation of its main downstream targets S6K1 and 4E-BP1. As enhanced mTORC1 activation following KE suggests higher protein synthesis rates, we used myogenic C2C12 cells to further confirm that ketone bodies increase both leucine-mediated mTORC1 activation and protein synthesis in muscle cells. Conclusion: Our results indicate that adding KE to a standard post-exercise recovery beverage enhances the post-exercise activation of mTORC1 but does not affect muscle glycogen resynthesis in young healthy volunteers. In vitro, we confirmed that ketone bodies potentiate the increase in mTORC1 activation and protein synthesis in leucine-stimulated myotubes. Whether chronic oral KE intake during recovery from exercise can facilitate training-induced muscular adaptation and remodelling need to be further investigated.